Cyber Harassment: Fenomena Hate Comment Di Era Pandemi Covid-19 Pada Akun Tik-Tok @Y***Q - Ahmad Hidayah; Yeni Marcelawati; Hanafi Saputra (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2021)
The era of the covid-19 pandemic, the popularity of social media shows an increasingly significant trend, especially in Indonesia. This fact is directly proportional to the emergence of various kinds of social media that offer various interesting features, one of which is the Tik-Tok application. Along with its development, many internet citizens (netizens) have used the comment feature on the content presented in the Tik-Tok application. However, this feature is used as a vehicle for self-existence through comments that are vulnerable to being included in the cyber-harassment category. This article tries to elaborate on the case of cyber harassment in the Tik Tok application in the form of hate comments on the @y***q account that occurred during the covid-19 pandemic era. Based on the theoretical framework of Social Identity, it can be explained how the phenomenon of cyber harassment is present as a consequence of technological developments which ultimately leads to Kekerasan Berbasis Gender Online (KBGO). Tik-Tok as social media is not friendly in presenting a gendered space that is used by women to express themselves through video content wrapped in the existence of self-identity, opposing discrimination, and denying the perpetuation of the definition of beautiful women based on other people's constructions (netizens).